Hydro- and sediment dynamics in a cold-water coral reef: insights from a 3D numerical model - Bartzke, Gerhard; Hebbeln, Dierk; Huhn, Katrin (Frontiers in Marine Science, 2025)
IntroductionCold-water coral reefs shape their surrounding environment by modifying local hydrodynamics and sediment dynamics, which in turn influence reef development and mound formation.MethodsThis study employs a three-dimensional Computational Fluid Dynamics (CFD) model, implemented in OpenFOAM, to investigate how the coral colonies influence near-bed flow and sediment transport processes at centimeter-to-meter scales. The simulated coral framework, composed of twelve colonies arranged in a 3×4 grid, was exposed to steady ambient flow conditions and a uniform sediment supply, to capture velocity fields, turbulent kinetic energy (TKE), and sediment concentration patterns.ResultsResults reveal that coral structures induce spatial flow heterogeneity, generating turbulent zones near stems that drive sediment resuspension and low-velocity, where low-turbulence areas promote deposition. Inter-coral gaps emerge as primary depositional zones, where low turbulence facilitates sediment accumulation.DiscussionThis underscores the pivotal role of coral morphology in directing sediment pathways and demonstrates how small-scale hydrodynamic processes govern localized deposition. By linking small-scale hydrodynamics with sediment dynamics, these findings suggest the early stages of mound aggradation, advancing understanding of the physical processes supporting cold-water coral reef development.